UAM 활성화를 위한 삼성역 부근의 버티포트 입지 분석 : 수도권 실증노선을 중심으로 - 김진식; 구병수; 남문주; 장국진; 이혜영; 이주연; 정명석 (시스템엔지니어링학술지, 2023)
This paper introduces urban air mobility (UAM) and the definition and types of vertiports required for UAM operations. It also examines domestic policy trends related to UAM and identifies UAM routes in Seoul currently planned by the government. To do so, we reviewed prior research on vertiports, analyzed new regulations from the European Aviation Safety Agency, and studied domestic vertiport specifications and deployment plans for UAM operations based on the size of the S-A1 airframe being developed by Hyundai, and applied them to Samsung Station, the core area of the demonstration routes. Next, using the 'Travel Time Savings Ratio', a method for evaluating transportation economics, we compared and analyzed the time taken by passenger vehicles and the time saved by using UAMs to derive a highly economical demonstration route. As a result, the Samsung Station↔Cheongnyangri Station section was found to be the most efficient. These findings are expected to be utilized for adjusting the distribution of UAMs when operating the demonstration route in the future.
Keywords: UAM; Vertiport; Feasibility; Travel Time Savings Ratio; Demonstration Route